Manajemen Sarana Pembelajaran Melalui Kebijakan Penggunaan Alat Elektronik dalam Mendukung Pendidikan Ganda di Pondok Pesantren Mannallah - Umi Habibah; Ahmad Syawal; Sedya Santosa; Musdalifa, Musdalifa (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the management of learning facilities through electronic device restriction policies in supporting dual education at Pondok Pesantren Mannallah. Dual education that integrates diniyah and formal curricula creates complexity in facility needs, especially when pesantren implements strict restrictions on the use of electronic devices. This qualitative research with a case study design involves 29 santri and 5 administrators as research subjects selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles, Huberman & Saldana model. The research results show: (1) the condition of learning facilities is still conventionally oriented with significant limitations in digital facilities there are no shared computers for santri, internet access is very limited, and the management system is manual-based; (2) the implementation of electronic device restriction policy creates a pedagogical paradox that is effective in maintaining the focus of diniyah learning but hinders the fulfillment of formal education needs; (3) optimization strategies require a controlled digital access model that provides controlled technology facilities without sacrificing pesantren values. The practical implications of this research recommend the provision of digital learning spaces with scheduled access, monitoring systems based on direct supervision, and integration of digital literacy into the pesantren curriculum as solutions to balance value preservation with 21st-century learning technology adaptation.